2017
DOI: 10.1007/s10620-017-4652-5
|View full text |Cite
|
Sign up to set email alerts
|

Nearly a Third of High-Grade Dysplasia and Colorectal Cancer Is Undetected in Patients with Inflammatory Bowel Disease

Abstract: The prevalence of previously undetected HGD/CRC in IBD found at colectomy was 29%. The high proportion of undetected rectal and right-sided HGD/CRC suggests that these areas may need greater attention during surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Patients with long-standing ulcerative colitis (UC) and Crohn's disease (CD) are at a higher risk of developing CRC compared to the general population. 5 Although IBD-associated CRC accounts for approximately 2% of all CRC, the rate of death resulting from CRC in IBD patients ranges from 10 to 15%. 6 he incidence rate corresponded to a cumulative probability of 2% by 10years; 8% by 20 years; and 18% by 30years.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with long-standing ulcerative colitis (UC) and Crohn's disease (CD) are at a higher risk of developing CRC compared to the general population. 5 Although IBD-associated CRC accounts for approximately 2% of all CRC, the rate of death resulting from CRC in IBD patients ranges from 10 to 15%. 6 he incidence rate corresponded to a cumulative probability of 2% by 10years; 8% by 20 years; and 18% by 30years.…”
Section: Discussionmentioning
confidence: 99%
“…A subset of dysplastic lesions may be followed up with continued surveillance instead of immediate surgical resection. Nevertheless, the persistent problems of interval carcinomas and undetected carcinomas and dysplasia highlight that endoscopic surveillance may not be feasible for all patients [79][80][81].…”
Section: Discussionmentioning
confidence: 99%
“…Cleveland et al [80] from the University of Chicago reported that for colectomy specimens resected for dysplasia or neoplasia identified on high-definition endoscopy in patients with inflammatory bowel disease between 2005 and 2014, synchronous invasive carcinoma was present in only 1 (3%) of 36 patients, but 8 (22%) patients had missed synchronous lesions of low-grade dysplasia or high-grade dysplasia. Eluri et al [81] from Johns Hopkins Hospital looked at resected specimens with high-grade dysplasia or carcinoma from patients with inflammatory bowel disease between 1994 and 2013 and found that in 70 patients 20 had either high-grade dysplasia or invasive carcinoma, which was missed on endoscopy (15 cases of high-grade dysplasia, 5 of carcinoma). Notably, there was no clear trend toward a decline in the proportion of undetected carcinoma or high-grade dysplasia over time, although correlation with high-definition endoscopy or chromoendoscopy could not be precisely determined.…”
Section: Surveillance Per the Scenic Guidelines And Associated Contromentioning
confidence: 99%
“…Indeed, there is evidence that 12% of abnormalities, such as colonic polyps, will be missed on a single endoscopy. A recent study from the United States found that high‐grade dysplasia or colorectal cancer undetected on colonoscopy but found at colectomy was as high as 29% . The main distribution of such lesions was in the rectum and on the right side of the colon, possibly the least well‐evaluated areas on routine colonoscopies.…”
Section: Effectiveness Of Surveillancementioning
confidence: 99%